Analyzing public sentiment on implementing the presidential threshold in Indonesia's presidential election system - Gustiawan, Randa; Rafzan, Rafzan; Ropawandi, Doni; Suswanta, Suswanta; Pribadi, Ulung (Universitas Negeri Yogyakarta, 2023)
The threshold Limits for presidential and vice presidential candidates have been a prominent topic since the introduction of direct presidential elections. Initially, the presidential threshold aimed to determine the candidates competing in the presidential election. However, over time, it has become a subject of prolonged debate, as it was perceived to undermine the rights of individuals in government and impede the principle of equality in democracy. This study utilizes qualitative research methods to gauge public sentiment regarding implementing the presidential threshold in Indonesia's presidential election system after the 2019 election. The research collected data through the Nvivo 12 Plus, utilizing sources such as Twitter (with the hashtag #presidentialthreshold) and online news media outlets, including Kompas, Detik, Tempo, Republika, and TribunNews. The study findings indicate that the percentage requirement is the most frequently discussed topic regarding the presidential threshold. Tempo is the online news media outlet that prominently highlights the issue. The analysis reveals that negative sentiment prevails in public opinion, comprising 63% of responses, while positive sentiment constitutes 37%. Tempo primarily represents positive sentiment, while Republika reflects negative sentiment. Positive public sentiment focuses on parliamentary support, while negative sentiment centers around candidates' opportunities.